The Role Of Social Capital In Community Based Drinking Water Programs in Sranak Village, Bojonegoro - Kukuh Nur Cahyo, Moh.; Rizal Sutikno, Fauzul; Rini Dwi Ari, Ismu (Fakultas Teknik, Universitas Brawijaya, 2024)
The ability of a community to manage water supply networks is significantly influenced by the type and extent of social capital, which helps to elucidate interaction patterns within water supply community groups. In 2018, Sranak Village in the Trucuk District became the first to implement the PAMSIMAS 7 Sumber program. This initiative involved community groups responsible for managing the program, with water network installations being independently distributed and maintained by the private sector. This research aims to assess the distribution of social capital and the level of community participation to enhance community-based water and sanitation management in Sranak Village. Utilizing Social Network Analysis (SNA), this study maps and examines the connections, networks, and information flows within the community. Data collection includes primary sources through direct observation and secondary sources from community water management groups. The findings reveal that Sranak Village possesses a robust social network and high levels of trust, which contribute to the effective management of water supply infrastructure. Moreover, social capital plays a crucial role in bridging gaps between community groups, thereby fostering development and sustainability. The study underscores the importance of social capital in community-based initiatives and suggests that enhancing these networks can lead to improved management and sustainability of water and sanitation systems.